Dry destillers grains in the multiple supplements for grazing nellore bulls - Silva, Yasmim Rodrigues Vilas Boas e (2019)
The objective of first study was to evaluate increasing levels of inclusion of dry distillery grains (DDG) in substitution of corn and urea in multiple supplements for beef cattle in good quality pasture of Urocloa brizantha cv. Marandu on the intake, digestibility, and efficiency of microbial synthesis and use of nitrogen. Were used four bulls Nellore cannulated in the rumen with an average age of 24 months and 445.12 ± 34.4 kg of body weight (BW), in a 4x4 Latin square design. Supplements differed by the inclusion level of DDG (0%, 31.5%, 63.0% and 94.5%). Increasing levels of DDG inclusion decreased dry matter intake (DMI) (P = 0.002), forage (P=0.002), organic matter (OM) (P=0.001), crude protein (CP) (P=0.037) and total digestible nutrients (TDN) (P<0.001), and had a quadratic effect on the intake of no fibrous carbohydrates (NFC) (P=0.002). It was observed an increase in the digestibility of ether extract (EE) (P = 0.005), however a decrease in the digestibility of NFC (P=0.001). Inclusion of DDG did not influence ruminal pH. There was a quadratic effect at collection times for ruminal ammoniacal nitrogen (P<0.05), except for the supplement with 94.5% DDG where the effect was linear (P=0.002). Nitrogen intake was 10.9% higher when there was no DDG in the supplement, compared to the supplement with 94.5% DDG (P=0.039). The excretion of N by feces was greater when there was a greater amount of DDG in the supplement (P=0.027), the opposite occurred with urine excretion of N, being higher when there was less amount of DDG in the supplement (P=0.027). Increasing levels of DDG did not affect ruminal microbial protein yield (P>0.05). The dried distillery grains can be used as an ingredient of multiple supplements as long as nutritional adjustments are made. The objective of second study was to evaluate the influence of higher levels of dry distillery grains (DDG) for beef cattle at pastures on in situ and in vitro ruminal degradability of dry matter (DM) and neutral detergent fiber (NDF) components of diets. In the in situ experiment, four Nellore bulls ruminally cannulate with mean age and weight of 445.12 ± 34.4 kg and 24 months were used, respectively, in a 4x4 Latin square delineated in paddocks formed of Urochloa brizantha cv. Marandu. The supplements (fed at 0.42% BW) were composed of crescent levels of DDG inclusion (0%, 31.5%, 63.0% or 94.5% of DDG in the supplement) to replace corn and urea. In the in situ experiment, 2 g of corn, DDG and forage masticate ground to 2 mm were placed in separate bags of WNW and were introduced directly into the rumen, in decreasing order of: 96, 72, 48, 24, 12, 6 and 3h. The bag residues were analyzed for dry matter content and neutral detergent fiber. DDG levels are not limited to generating in situ digestibility of DM and NDF from the ingredients. The in vitro experiment was carried out using the ruminal content of two Nellore bulls (BW = 450 kg and 435 kg) supplemented with concentrate (2 kg /animal/day). Were evaluated forage, supplements containing 0%, 31.5%, 63.0% or 94.5% of DDG and the diets (77% of forage and 23% of supplement). The volume of gas produced was recorded after 2, 4, 6, 12, 18, 24, 30, 36, 48, 60, 72 and 96 hours. All the vials were removed at the 96 hours incubation time, its content was used to determine in vitro dry matter digestibility (IVDMD) and neutral detergent fiber (IVNDFD). Increasing DDG levels did not influence kinetic parameters of in situ digestibility (P>0.05). In vitro gas production was lower for both diets and supplements containing more DDG and forage (P>0.05). DDG levels did not influence digestion rate (Kd), half-life (HL), or curve inflection time (Inf) (P>0.05). However for the diet components, the forage had higher HL and Inf (P<0.05). IVDMD had a linear effect on both diets and supplements with increasing levels of DDG (P<0.01), whereas IVNDFD had a quadratic effect also for supplements and diets (P<0.05). Supplements and diets with increasing levels of DDG have lower in vitro digestibility of DM and the production of gas.